An exploratory study on Project-Based Learning (PBL) in tertiary ESL classrooms in India: Teachers’ insights on adoption and challenges - Meera, A.; Venkatalakshmi, T. Shrimathy; Raja Durai, K. Denish; Singh, S. Kavita (Research Journal in Advanced Humanities, 2025)
Project-Based learning (PBL) has gained significance in English as a Second Language (ESL) education due to its efficacy in real time language acquisition. This study explores the ESL teachers’ perceptions of PBL, emphasising its implementation, impact, challenges and training at the tertiary level particularly engineering colleges in Tamil Nadu, India. Data were collected through questionnaire from 75 ESL teachers from engineering colleges. Further, to corroborate the questionnaire results, interviews were conducted with 15 teachers. The findings show that the ESL teachers show a positive attitude towards PBL however there exists a gap between knowledge and practice due to many challenges like large class size, rigid curriculum and limited proficiency students. Teachers emphasised the positive impacts in the teaching learning process. They also stressed the need for teachers training, institutional support for effective integration PBL in ESL classrooms.